Gallbladder carcinosarcoma accompanied with bile duct tumor thrombi: A case report - WANG, YAN (D.A. Spandidos, 2013)
Gallbladder carcinosarcoma is one of the rarest subsets of gallbladder malignancies. The first case of carcinosarcoma of the gallbladder was reported in 1907. To date, <100 cases have been reported in the English literature. The present study reports a case of gallbladder carcinosarcoma accompanied with tumor thrombi, presenting as a soft tissue mass in the common bile duct and resulting in the obstruction and inflammation of the biliary tract. Initially, the patient was diagnosed with a gallbladder tumor and choledocholithiasis. No cases of carcinosarcoma of the gallbladder accompanied with bile duct tumor thrombus formation have been reported to date. A cholecystectomy with liver segmentectomy (S4a+S5) and a lymph node dissection were performed. The presence of a tumor thrombus in the common bile duct was confirmed by analysis of a frozen section during surgery. Resection of the extrahepatic bile duct and Roux-en-Y type hepatic cholangiojejunostomy were also performed. In addition, the gallbladder carcinosarcoma was observed to produce α-fetoprotein. The patient underwent an uneventful post-operative recovery and, to date, no clinical or radiological evidence of disease recurrence or metastasis has been identified. Carcinosarcoma of the gallbladder accompanied with tumor thrombi is extremely rare. Tumor thrombi in the common bile duct may easily be misdiagnosed as choledocholithiasis. The treatment and prognosis of gallbladder carcinosarcoma is similar to that of gallbladder carcinoma.